INTEGRASI NILAI KEPEMIMPINAN NABI MUHAMMAD SAW DALAM MODEL TRANSFORMATIONAL DAN SERVANT LEADERSHIP - Dikriyah; Suprihatin (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2025)
Abstract: Leadership is an important aspect in building civilisation and social change. In the modern context, two widely discussed leadership models are Transformational Leadership and Servant Leadership. Both models have values that are in line with the principles of leadership in Islam as taught in the Qur'an and exemplified by the Prophet Muhammad (peace be upon him). This study aims to analyse the relationship between these two concepts and the verses of the Qur'an that emphasise the values of compassion, justice, exemplary behaviour, deliberation, and social responsibility. The results of the study show that Transformational Leadership is reflected in the visionary and inspirational leadership of the Prophet Muhammad (peace be upon him), which transformed society for the better (QS. Al-Imran [3]:159; QS. Al-Anbiya [21]:107), while Servant Leadership is reflected in his humble attitude, serving the people, and upholding justice (QS. Al-Furqan [25]:63; QS. Al-Ma'idah [5]:8). Thus, Islamic leadership is able to integrate transformational and service values into a unified Qur’anic leadership ethic. Keywords: Islamic leadership, transformational leadership, servant leadership, Al-Qur’an